1982
DOI: 10.1021/jm00350a017
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic agents. 5. Synthesis and anthelmintic activities of novel 2-heteroaromatic-substituted isothiocyanatobenzoxazoles and -benzothiazoles

Abstract: The synthesis and antiparasitic properties of 22 isothiocyanato-2-pyridinylbenzoxazoles and benzothiazoles are described; the preparation and anthelmintic activities of 14 isothiocyanato-2-thienyl-, -furyl-, and -pyrrolylbenzoxazoles are outlined. In mice experimentally infected with Nematospiroides dubius (nematode) and Hymenolepis nana (tapeworm), three derivatives, i.e., 5-isothiocyanato-2-(2-furyl)benzoxazole (34), 5-isothiocyanato-2-(5-methyl-2-furyl)benzoxazole (35), and 5-isothiocyanato-2-(1-methyl-1H-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…For example, 24DNBA has been evaluated as a precursor for carbamates used in the synthesis of tumor treatments (3) and antibiotic prodrugs (9); hence, the 23DNBA product synthesized as described in this report from 23DNT, which is not commercially available, may be useful as a precursor. In addition, isomers of 4-amino-2-nitrocresol (generated here from the oxidation of 4A2NT) such as 6-amino-4-nitro-o-cresol and 2-amino-5-nitrop-cresol have been evaluated as a precursors for fungicides (42) and antiparasitic agents (8), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 24DNBA has been evaluated as a precursor for carbamates used in the synthesis of tumor treatments (3) and antibiotic prodrugs (9); hence, the 23DNBA product synthesized as described in this report from 23DNT, which is not commercially available, may be useful as a precursor. In addition, isomers of 4-amino-2-nitrocresol (generated here from the oxidation of 4A2NT) such as 6-amino-4-nitro-o-cresol and 2-amino-5-nitrop-cresol have been evaluated as a precursors for fungicides (42) and antiparasitic agents (8), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…2-Methylbenzoxazole (31) reacts with benzaldehyde in the presence of zinc chloride to give the 2-benzylidene derivative (41) indicating the reactivity of the methyl group linked to azomethine system. (42) is reactive enough to couple with diazonium salts and reacts at the 2-methylene group with aldehydes, nitroso compounds, and amyl nitrite.…”
Section: Jyothi and Merugumentioning
confidence: 99%
“…Benzoxazoles substituted at G-2 were prominently studied (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) trusting that this position is decisive for the biological activity. Evans et al showed that para substituted 2-aryl-5-benzoxazolealkanoic acid derivatives had the highest activity compared to its analogs (12,13).…”
Section: Key Word Indexmentioning
confidence: 99%